EKSPRESI TNF-α DAN CALCINEURIN PADA ASIMTOMATIS APIKAL PERIODONTITIS AKIBAT INDUKSI Enterococcus faecalis - Randy Carlos Sietho; Mandojo Rukmo; Edhie Arif Prasetyo; Tamara Yuanita (Universitas Airlangga, 2017)
Background. Gram positive bacteria strain are the major cause of endodontic failure as asymptomatic apical periodontitis. One of the dominant group of bacteria is Enterococcus faecalis that still persistent in root canal system post endodontic therapy procedures. This bacteria has lipoteichoic acid on its membrane that can cause induction of cytokines expression such as Tumor Necrosing Factor-α (TNF-α) and Calcineurin Purpose. This experiment to demonstrated asymptomatic apical periodontitis that induced with Enteroccus faecalis produce raising amount of TNF-α and Calcineurin expression cells in pericapical tissue of wistar rat. Method. The upper right molar teeth of the rat was drilled until perforation then exposed by BHIB 10µl (control positive group), E.faecalis 106 CFU in BHIB 10µl (experimental group) and without drilling (control negative group) then observed until 21th days and counting the amount of TNF-α and Calcineurin expression cells. Conclusion.The results show that asymtomatic apical periodontitis that was induced E.faecalis produce increasing amount of TNF-α and Calcineurin expression cells in periapical tissue wistar rat.